Efeitos fisiológicos do treinamento físico de Krav Maga nas variáveis: hemodinâmica, metabólica, hidratação, neuromuscular, hormonal e sono - ANDRADE NETO, João Batista de (2019)
Introduction: Krav Maga is a fighting modality developed in Israel in the 1940s. As Physical Training it is considered an acyclic modality alternating aerobic and anaerobic exercises, stimulating and causing acute stress and chronic changes to the physiological systems. Materials and Methods: Thirty (30) men participated in the intentional research, divided into two groups: GI = 15, beginners / control and GV = 15 veterans, aged between 30.73 ± 11.84, all from Teresina-PI. The Krav Maga protocol was applied in 16 weeks, with 3 weekly sections, progressively varying from 60 to 90 minutes, with basic teaching techniques, adjusted every 8 weeks. Five questionnaires were applied: Adherence; Socioeconomic; Motivation - (PMQ); Pre-competitive anxiety - CSAI-2; and Anthropometric Assessments: Calculation of Body Mass Index - BMI; Waist-Hip Relationship (WHR); Body Fat with 7 folds; Blood Pressure (PAS; PAD); Heart Rate (HR) and Double Product (DP); Maximum Oxygen Consumption - VO2 max; Lumbar and Joint Flexibility; Muscular Strength: Isometric Handgrip of upper limbs and Total Free Force; Urine hydration with refractometer; Muscular endurance (abdominal test and flexion of arms on the ground); Metabolic (blood) for Lipid Profile (total cholesterol, HDL cholesterol, LDL, VLDL, triglycerides) and Glucose; Pre- and post-training blood glucose, Cortisol, Lactated and Pittsburgh Sleep Quality (PSQI). Results an Discussion: At the end of the application of Krav Maga Physical Training, and data analysis, it was verified that the protocol caused changes in the minimum, maximum, average and standard deviation values of the following markers: Weight (Kg) of GI = 3.2 and GV = 1.6 kg; BMI (Kg / m2) of GI = 1.0 and GV = 1.0; WHR (cm) of GI = 0.1 and GV = 1.0; Density (g / ml) GI = 0.1 and GV = 1.0; Body Fat% of GI = 1.6 and GV = 3.7; Lean Mass (Kg) GI = 1.0 and GV = 2.5; Fat Mass (Kg) of GI = 4.4 and GV = 2.3; Blood Pressure - SBP (mmHg) GI = 6.8 and GV = 7.8, DBP (mmHg) GI = 0.6 and GV = 3.6; HR (bpm) GI = 4.0 and GV = 2.6; MAP (mmHg) GI = 10.1 and GV = 6.5; VO2max GI = 1.0 and GV = 1.1; Total Cholesterol (mg / dL) GI = 3.1 and GV = 12.6; Triglycerides (mg / dL) 1.04 and GV = 32.6 Glucose Fast GI = 18.5 and GV = 4.2; HDL (mg / dL) GI = 0.6 and GV = 1.3, LDL GI = 4.3 and GV = 10.4, VLDL GI = 2.2 and GV = 2.1; Glucose pre and post (mg / dL) GI = 20.5 and GV = 6.4; Hydration GI = 0.3 and GV = 0.2; Palmar Grip Force (Kg / f) GI = 3.0 and GV = 2.7 both hands; Total Free Force: Back Squat (kgf) GI = 12.1 and GV = 16.4; Deadlifit GI = 9.4 and GV = 11.8; Shoulder Press GI = 5.0 and GV = 8.0; Flexibility (cm) GI = 6.3 and GV = 5.6; Lactate (mmol / L) GI = 3.0 and GV = 1.0, Cortisol GI = 0.6 and GV = 1.0; Sleep 100% improvement. Conclusion: It was found that the training protocol applied caused physiological changes in all variables studied: reduced levels of anxiety; percentage of fat and BMI; the WHR measures; modified aspects of body composition; it caused elevations in MAP and PD, triggering elevations in HR, PAS and DP; improved VO2 max cardiorespiratory fitness; increased flexibility; it caused an increase in the strength of the upper limbs; total free force; improved hydration practice; increased muscle endurance; decreased the rates of total cholesterol and triglycerides; improved the lipoprotein profile, induced an increase in cortisol secretion; stimulated lactate removal and improved sleep quality.